1996
DOI: 10.1111/j.1365-2044.1996.tb07854.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide: an unusual cause of arterial and venous gas embolism

Abstract: SummaryA patient undergoing minor orthopaedic surgery suffered from unexpected arterial and venous gas embolism caused by hydrogen peroxide. We describe our management of the case and emphasise the need for continued vigilance during the use of hydrogen peroxide. Key wordsComplications; embolism, oxygen. Pharmacology; hydrogen peroxide.The use of hydrogen peroxide has been associated with a variety of potentially fatal complications such as surgical emphysema and oxygen embolism to various vascular beds of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Human catalase is highly efficient, mediating the breakdown of up to 200,000 molecules of hydrogen peroxide per second 2,5 . One millilitre of 3% hydrogen peroxide solution will produce 9.8 millilitres of oxygen 6,7 .…”
Section: Pharmacologymentioning
confidence: 99%
See 1 more Smart Citation
“…Human catalase is highly efficient, mediating the breakdown of up to 200,000 molecules of hydrogen peroxide per second 2,5 . One millilitre of 3% hydrogen peroxide solution will produce 9.8 millilitres of oxygen 6,7 .…”
Section: Pharmacologymentioning
confidence: 99%
“…There are approximately 62 cases described in the international literature of severe morbidity and mortality resulting from intraoperative oxygen embolism, but only two in the Australasian literature 2,6, . This is despite the fact that in the latest report of the Victorian Consultative Council on Anaesthetic Mortality and Morbidity hydrogen peroxide solutions were specifically mentioned in three cases of oxygen embolism 59 .…”
Section: Oxygen Embolismmentioning
confidence: 99%
“…Application of H 2 O 2 to human tissue causes it to rapidly decompose into oxygen and water. 2 5 It has been reported that as little as 1 mL of 3% H 2 O 2 can release up to 10 mL of oxygen. 4…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Patients with cardiac shunts (foramen ovale, atrial or ventricular septal defect) are at even higher risk of air embolism resulting in lethal cardiac or respiratory events. 5 Prior authors have cautioned the use of H 2 O 2 in confined spaces due to increased risk of air embolization. 1,2,4 It is believed that the sudden production of gas in an enclosed area results in increased pressure, thereby forcing gas into the blood stream.…”
Section: Risksmentioning
confidence: 99%
See 1 more Smart Citation